Приватні керуючі компанії - нові учасники житлово-комунального господарства України - Доненко, В. І. (Ways to Improve Construction Efficiency, 2013)
Article considers the basic needs of housing and communal services of Ukraine and their solutions. The present models of housing in the world. Based on the research proposed mechanisms for effective functioning of private management companies in Ukraine.